Perception of Health Promotion Practices Among the Faculty of Selected University, Ras Al Khaimah, United Arab Emirates (International Journal of Studies in Nursing, 2019)
Background and aim: Health promotion is one of the vital and key element for a healthy living. The health care professional spent their initial developing years in learning about health and thereafter training and imparting knowledge to their students and people to whom they serve. The faculty of health sciences are the educators who not only teach health promotion to their students but also educate and prepare the students for the health promotion of the society. Aim: The purpose of the study was to assess the perception of health promotion and health promotion practices existing among the faculty of Medical and Health Sciences University, Ras Al Khaimah, UAE. Study design: The study was descriptive and cross sectional. Data was collected using convenience sampling technique. Self-administered questionnaire was used for data collection. The sample size of the study was 52. Results: Of the total 52 respondents, majority were females, 31-50 years old (63%), married (87%) from nursing and medical faculty ( 63%), non arabic (77%), with 20 or less years of total professional experience(62%). About 52% of the faculty reported that their daily routine comprises sitting at one place for 6-10 hours. Majority (98%) of the participant felt that health promotion is most important for healthy living and is the best resource for everyday life (100%). However majority (60%) of the faculty reported that they do not find time to perform health promotion activities especially daily physical exercises and only 39% were actually able to perform their daily exercises. CONCLUSION: Though health promotion activities are most important for healthy living, the physical exercises as essential health promotion activities are not practiced by the health sciences university faculty.